Conversions of Benzoxazinoids and Downstream Metabolites by Soil Microorganisms - Schütz, Vadim; Bigler, Laurent; Girel, Sergey; Laschke, Laura; Sicker, Dieter; Schulz, Margot (Frontiers in Ecology and Evolution, 2019)
Benzoxazinoids, secondary metabolites of several Poaceae, and some benzoxazinoid downstream metabolites are bioactive compounds that act as allelochemicals and natural pesticides. Since a short lifetime of the substances is crucial to avoid long-term environmental effects, total degradation by microorganisms is of exceptional importance. We performed a screening with cultivable microorganisms (Species names and strain numbers: Mycobacterium fortuitum, 7; Bacillus aryabhattai, 34; Bacillus cereus, 59; Bacillus megaterium, 21, 48; Bacillus methylotrophicus, 58; Lysinibacillus xylanilyticus, 56; Paenibacillus polymyxa, 51; Aminobacter aminovorans, 49; the fungi Papulaspora sepedonioides, 12 and Trichoderma viride, 47) isolated from soil previously used for wheat and Persian clover mixed-culture systems to assess their behavior in the presence of the compounds. The microorganisms were exposed to glucosylated benzoxazinones, the benzoxazinones HBOA, DIBOA and DIMBOA, the benzoxazolinones BOA, BOA-6-OH, and MBOA, and to several downstream products (AP, AAP, oHPMA, glucoside carbamate) in liquid culture to avoid interferences with soil minerals and other organisms. The microorganisms differed strongly in their metabolic activities in terms of growth, compound modification, and degradation. We observed degradation with DIBOA and GDIMBOA but rarely with DIMBOA, whereas BOA and MBOA showed almost no degradation when directly applied. Hydroxylation of BOA and demethylation of MBOA by the plant, resulting in BOA-6-OH, activated the benzoxazolinones for bacterial nitration. The resulting NBOA-6-OH was short-lived but could function temporarily as an allelochemical by inhibiting photosynthesis, e.g., in young seedlings of cress and kohlrabi. The BOA downstream products AP and oHPMA were converted to AAP, which can be nitrated to N-(2-OH-5-nitrophenyl)-acetamide and then degraded by A. aminovorans (49) and P. polymyxa (51). Only P. sepedonioides (12) and P. polymyxa (51) failed in the conversion of HBOA into AAP. While DIBOA, DIMBOA, MBOA, NBOA-6-OH, AP, AAP, and oHPMA reduced the growth of most microorganisms, glucoside carbamate promoted their growth. GDIMBOA had a stimulatory effect towards the fungi and three bacterial species. These findings lead to the hypothesis that in a natural habitat, such as the root surface, microorganisms may cooperate, perhaps by involving the plant, for the successful elimination of benzoxazinoids and their downstream metabolites.